Second-generation immunotherapeutics in multiple sclerosis: can we discard their precursors?. Issue 2 (February 2021) - Findling, Oliver; Sellner, Johann
Highlights: Options for disease-modifying therapies in multiple sclerosis are emerging. Among these are second-generation therapeutics. The underlying concepts and prevailing unmet needs are introduced. Upcoming developments in the field of second-generation therapeutics are presented. Abstract : Options for disease-modifying therapies in multiple sclerosis have increased over the past two decades. Among these innovations are interferon-β, glatiramer acetate, fumaric acid and dihydroorotate dehydrogenase inhibitors, an antibody targeting the migration of immune cells, a compound that traps immune cells in lymphoid organs by sphingosine 1-phosphate receptor (S1PR) modulation and immune-reconstitution therapies. Second-generation drugs such as pegylated interferon-β, advanced CD20 depleting antibodies, more-specific S1PR modulators and new formulations have been developed to achieve higher efficacy while exhibiting fewer side effects. In this review, we address the shortcomings of the parent drugs, present the pros and cons of the second-generation therapies and summarize upcoming developments in the field of immunotherapy for multiple sclerosis.